Investigating EFL Students’ Speaking Difficulties through Peer Feedback Comments on Tiktok Videos - Siti Amsyiyah; Irmayani Irmayani; Anita Dwi Hapsari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
Speaking skills are regarded as one of the most difficult skills to be acquired by EFL students, especially high school EFL students, because of language and psychological factors. This paper attempts to examine high school EFL students’ speaking difficulties as identified by peer feedback in TikTok speaking activities. Qualitative descriptive design was adopted in this study by involving 15 tenth-grade students in carrying out speaking activities in the form of recording TikTok video clips and commenting on their peers’ videos. The data obtained include speaking clips, peer feedback comments, and reflective statements of the participants, which were analyzed using a thematic analysis approach. The results found that there were four different types of speaking difficulties, namely fluency difficulties, pronunciation difficulties, organizational difficulties, and difficulties related to confidence and anxiety levels of students when conducting a speaking activity. This can be evidenced by the students’ hesitation, frequent pauses, mispronunciation, disorganized speaking, and lack of confidence when speaking. Peer feedback comments play an important role in discovering this problem pattern among high school EFL students.